Some Like It Hot: Maternal-Switching With Climate Change Modifies Formation of Invasive Spartina Hybrids - Gallego-Tévar, Blanca; Infante-Izquierdo, María D.; Figueroa, Enrique; Nieva, Francisco J. J.; Muñoz-Rodríguez, Adolfo F.; Grewell, Brenda J.; Castillo, Jesús M. (Frontiers in Plant Science, 2019)
Climate change can induce temporary, spatial or behavioral changes in species, so that only some species can adapt to the new climatic conditions. In the case of invasive species, it is expected that they will be promoted in a context of global change, given their high tolerance to environmental factors and phenotypic plasticity. Once in the invaded range, these species can hybridize with native species thus introducing their genotype in the native biota. However, the effects that climate change will have on this process of invasion by hybridization remain unclear. We evaluated the historical establishment of the reciprocal hybrids between the native Spartina maritima and the invasive S. densiflora in the Gulf of Cadiz (SW Iberian Peninsula) and we related it to climatic changes during the period 1955-2017. Our results showed that, according to their dating based on their rate of lateral expansion rates, the establishment of S. maritima x densiflora and S. densiflora x maritima in the Gulf of Cadiz has occurred in the last two centuries and has been related to changes in air temperature and rainfall during the flowering periods of their parental species, with antagonist impacts on both hybrids. Thus, the hybrid S. densiflora x maritima has been established in years with mild ends of spring and beginning of summer when the flowering of S. maritima lengthened and its pollen production was higher, and it coincided with the beginning of the flowering period of S. densiflora. Moreover, the establishment of this hybrid was related to higher spring/summer rainfalls, probably due to the reduction in salinity in middle marshes. However, the hybrid S. maritima x densiflora, was established mainly in warmer spring/summers in which the proportion of pollen:ovule of S. maritima was reduced favoring its pollination by S. densiflora. As a consequence of the promotion of S. maritima x densiflora with climate change, the native and endangered species S. maritima would be threatened, as both taxa share the same habitat and the hybrid shows a remarkably higher competitive potential.